Clinical Treatment of Pediatric Primary Cardiac Tumors: A Single-Institute 12-Year Experience. Issue 8 (November 2020) - Ding, Peicheng; Qi, Jirong; Mo, Ran; Sun, Jian; Pen, Wei; Wu, Kaihong; Qian, Longbao; Mo, Xuming
Abstract : Background: Primary cardiac tumors in children are extremely rare. This study aimed to analyze clinical treatment and follow-up of pediatric primary cardiac tumors. Patients and Methods: We performed a retrospective analysis by searching the medical records of 75 patients diagnosed with pediatric primary cardiac tumors from June 2005 to August 2017 in our institution. We followed operative patients every half year in the first postoperative year and then at least every year. If the patients had no serious symptoms or hemodynamic changes, they received nonoperative management and were followed regularly every year. Results: Nineteen patients underwent surgery at our department for serious symptoms and critical hemodynamic changes. Four patients had postoperative complications. Two died of low cardiac output syndrome and arrhythmia after surgery. One patient with myxomas had tumor recurrence and one had been found of another rhabdomyoma after surgery. The other 14 patients recovered well. Fifty-six patients had nonoperative management. Four were lost in follow-up. Two patients with malignant tumors died of unknown causes after discharge. The remaining patients had no severe symptoms or tumor growth during follow-up. Conclusions: Clinical treatment of pediatric primary cardiac tumors should be performed individually. Most pediatric primary cardiac tumors are benign, and spontaneous regression is possible, especially for rhabdomyomas. The principle purpose of surgical treatment is to restore normal hemodynamics and protect important structures and cardiac tissue.